Landmark guided internal jugular vein catheterization in infants undergoing congenital heart surgery - Seçici, Serkan (The European Research Journal, 2021)
Objectives: Central venous catheterization is an important procedure for infants undergoing heart surgery. Ultrasound-guided methods have been shown to decrease failure and complications. The goal of the present study was investigate the effect of anatomical landmark technique during internal jugular vein access in low-weight infants undergoing congenital heart surgery. Methods: A total 98 infants (median age was 16.5 days, median weight was 3275 g) who underwent internal jugular vein catheterization between January 2017 and October 2019 were retrospectively analyzed. All catherizations were performed by a pediatric heart surgeon. Data including demographic characteristics of the infants, success rate, and catheter-related adverse events were recorded. Results: Success rate was 94.9% (n = 93). There were three arterial puncture (3.1%) and hematoma occurred in five patients (5.1%). Central venous catheterization of 78 (79.6%) patients were successful at the first attempt. Conclusions: Our study suggest that landmark technique still seems useful by experienced operators and is safe and effective in infants weighing less than 5 kg undergoing congenital heart surgery.